A case report on Kikuchi disease - Waghray, Jyotika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Kikuchi-Fujimoto disease (KFD), or histiocytic necrotizing lymphadenitis, is a benign and self-limited disease that mainly affects young women. Patients present with localized lymphadenopathy, fever, and leukopenia in up to half of the cases. KFD can occur in association with systemic lupus erythematosus. We present the case of a patient with KFD and systemic lupus erythematosus. A 38 years old female presented with right sided cervical lymphadenopathy, fever and a rash on the face, with a loss of apetite and generalized body weakness. After a series of investigations to rule out other conditions like tuberculosis, a diagnosis of kikuchi disease was made based on the biopsy report. There was a strong suspiscion of SLE as well pertaining to the facial rash. An ANA profile was done which strongly indicated SLE as well. The patient was started on steroids and other systematic treatment and recovered gradually. With its shared clinical features, Kikuchi-Fujimoto disease can be mistaken for other forms of lymphadenitis. A combined use of medical imaging and laboratory tests is the effective way to avoid misdiagnosis.